2015
DOI: 10.1093/toxsci/kfv048
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug-Induced Liver Injury in Micropatterned Co-cultures Containing iPSC-Derived Human Hepatocytes

Abstract: Primary human hepatocytes (PHHs) are a limited resource for drug screening, their quality for in vitro use can vary considerably across different lots, and a lack of available donor diversity restricts our understanding of how human genetics affect drug-induced liver injury (DILI). Induced pluripotent stem cell-derived human hepatocyte-like cells (iPSC-HHs) could provide a complementary tool to PHHs for high-throughput drug screening, and ultimately enable personalized medicine. Here, we hypothesized that prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 36 publications
2
117
0
Order By: Relevance
“…Further studies are needed to find the best combination of these culture methods and cell types and improve the functions of hiPSC-derived hepatocytes. Recent studies reported that the micro-patterned co-culture methods enhanced the hepatic functions of hiPSC-derived hepatocytes and could be useful to screen for DILI (Berger et al, 2014;Ware et al, 2015). They seeded hiPSC-derived hepatocytes on the micro-patterned collagen in a microwell plate, and co-cultured them with murine fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to find the best combination of these culture methods and cell types and improve the functions of hiPSC-derived hepatocytes. Recent studies reported that the micro-patterned co-culture methods enhanced the hepatic functions of hiPSC-derived hepatocytes and could be useful to screen for DILI (Berger et al, 2014;Ware et al, 2015). They seeded hiPSC-derived hepatocytes on the micro-patterned collagen in a microwell plate, and co-cultured them with murine fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…While iPSCs require dedifferentiation with subsequent redifferentiation to derive appropriate cell lines, they provide an innovative way to both model liver disease and assess how certain polymorphisms may affect drug metabolism and disposition in vitro. Additionally, human iPSCs (hiPSCs) have a significant amount of commercial availability for applications in liver toxicity testing and have the potential to be used in coculture with hepatocytes and fibroblasts to give an accurate model for predicting potential liver toxicity [199201]. …”
Section: Towards Integrative Platforms For Comprehensive Iadr Predmentioning
confidence: 99%
“…More importantly, one of the most desirable characteristics needed for improving translational prospects of these cells is sustained functionality of a handful of the most important hepatic cytochrome P450 enzymes, since these CYP proteins are involved in metabolism and bioactivation of more than 75% of drugs [94]. Despite the fact that human PSC-derived hepatocytes are still characterized by lower CYP enzymatic activity when compared to fresh primary hepatocytes, these cells have already been demonstrated to be a valuable platform for hepatocyte-specific toxicity assays [95,96,97,98] (Table 1). Moreover, iPSC-derived hepatocytes exhibit high levels of other hepatic functions, such as synthesis and secretion of various plasma proteins (carrier proteins like albumin, blood clotting factors and apolipoproteins), glycogen storage, urea production, and bile production.…”
Section: Cytotoxicitymentioning
confidence: 99%